Activity-Based Protein Profiling Reveals Changes to the Regulation of Enzymatic Activity by the Hepatitis C Virus - Desrochers, Geneviève Ferraro (Université d'Ottawa / University of Ottawa, 2021)
Biological systems, their physical structure and their functions, are built, maintained, and controlled by the activity of enzymes. Understanding how enzymes contribute to the regulation of various pathways and processes allows us to gain a deeper understanding of the entirety of the biological system. As changes in enzyme activity are often essential for the pathogenesis of multiple and varied diseases, identifying these changes represents a crucial step to both understanding the disease and preventing its progression within the individual. Enzymes’ functional output can be controlled by numerous different mechanisms, including control of transcription and translation, subcellular localisation, co-factor interactions, or chemical modification to specific amino acids. Activity-based protein profiling allows the potential for activity of target enzymes to be measured, thereby gaining a more accurate representation of the functional state of the biological system. In this work, profiling differential enzyme activity allows the discovery of previously unknown links between metabolic regulatory enzymes and infection by the hepatitis C virus (HCV). The novel probe wortmannin-yne is described and is shown to be able to report on the activity multiple kinases, including MAPK1, whose activity is dysregulated during HCV replication. Novel probes designed to target a smaller selection of kinases, phosphatidylinositol kinases, are reported and are shown to be capable of measuring HCV-induced changes to not only kinase activity but also regulatory protein-protein interactions with the phosphoinositide kinases. Lastly, the role of microRNA-27b in the HCV-induced dysregulation of lipid metabolic enzymes is examined. Three novel targets of microRNA-27b are identified, and their dysregulation is shown to have an effect on the life cycle of HCV. Altogether, this work has developed new tools for the study of metabolic enzymes and identified new avenues of investigation into the dysregulation of lipid metabolism.
Keywords: Host-virus interactions; Activity-based protein profiling; Hepatitis C virus; Kinases; microRNA; miR-27b